2007
DOI: 10.1002/etep.205
|View full text |Cite
|
Sign up to set email alerts
|

Modelling volatility clustering in electricity price return series for forecasting value at risk

Abstract: SUMMARYModelling of non-stationary time series using regression methodology is challenging. The wavelet transforms can be used to model non-stationary time series having volatility clustering. The traditional risk measure is variance and now a days Value at Risk (VaR) is widely used in finance. In competitive environment, the prices are volatile and price risk forecasting is necessary for the market participants. The forecasting period may be 1 week or higher depending upon the requirement. In this paper, a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Empirical studies using these methods have reported positive performance [14]. Meanwhile, the recently emerging empirical mode decomposition (EMD) takes an empirical, intuitive, direct and self-adaptive data approach as the alternative [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies using these methods have reported positive performance [14]. Meanwhile, the recently emerging empirical mode decomposition (EMD) takes an empirical, intuitive, direct and self-adaptive data approach as the alternative [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Most of current approaches use the multi-resolution analysis capability of wavelet analysis to look into the past price or correlation behaviours in the capital markets [21,22], e.g., it has been used to analyze the risk distribution across differences the scales [23][24][25][26][27][28][29][30]. Some researches such as that by Karandikar et al [31] has gone a step further to estimate VaR with this information taken into account. VaR estimated following the traditional approaches is adjusted by the proportion of risks that corresponds to the investment time horizon [31].…”
Section: Introductionmentioning
confidence: 99%
“…Some researches such as that by Karandikar et al [31] has gone a step further to estimate VaR with this information taken into account. VaR estimated following the traditional approaches is adjusted by the proportion of risks that corresponds to the investment time horizon [31]. These approaches are unique in that VaRs are tailored to investor's investment profile [24].…”
Section: Introductionmentioning
confidence: 99%
“…have recently attracted significant research attention in the risk measurement literature. For example, [12] combined the wavelet analysis and regime switching model to estimate electricity VaR. However, the performance of the wavelet-based approach is constrained by the limited amount of wavelet basis available in the literature.…”
Section: Introductionmentioning
confidence: 99%